Análise jurídico-penal da Lei N. 9.605/1998 e a proteção do meio ambiente - Totoli, Stella Soutto Mayor (2023)
The present study deals, essentially, with the analysis of the Brazilian Federal Law n. 9.605/98, which typifies crimes committed against the environment, under a legal-criminal approach. Based on this analysis, the researcher intends to verify whether the beforementioned infraconstitutional law is, in fact, efficient in properly protecting the environment. The dissertation begins with an interdisciplinary examination of the concept of environment and the need for its adequate protection, as a way of also safeguarding the dignity of the human person. In later chapters, the researcher will evaluate the treatment given to the subject in Brazil, both in the constitutional and infraconstitutional-criminal scope, and in the World, based on comparative law analysis. It will also expose emblematic cases of environmental crimes in Brazil, which occurred in the years 2015, 2019 and 2020, drawing a parallel with the jurisprudence of some Courts in the country on the subject, in order to analyze whether there is effective punishment of agents who commit crimes against the environment, with regard to the retributive and preventive aspects of penalties. In the conclusions, some of the researcher's suggestions will be presented, aiming to reduce impunity and discourage the commission of crimes against the environment